Induced Systemic Resistance against Botrytis cinerea by Bacillus cereus AR156 through a JA/ET- and NPR1-Dependent Signaling Pathway and Activates PAMP-Triggered Immunity in Arabidopsis - Nie, Pingping; Li, Xia; Wang, Shune; Guo, Jianhua; Zhao, Hongwei; Niu, Dongdong (Frontiers in Plant Science, 2017)
Induced resistance response is a potent and cost effective plant defense against pathogen attack. The effectiveness and underlying mechanisms of the suppressive ability by Bacillus cereus AR156 to Pseudomonas syringae pv. tomato DC3000 (Pst DC3000) in Arabidopsis has been investigated previously; however, the strength of induced systemic resistance (ISR) activity against Botrytis cinerea remains unknown. Here, we show that root-drench application of AR156 significantly reduces disease incidence through activation of ISR. This protection is accompanied with multilayered ISR defense response activated via enhanced accumulation of PR1 protein expression in a timely manner, hydrogen peroxide accumulation and callose deposition, which is significantly more intense in plants with both AR156 pretreatment and B. cinerea inoculation than that in plants with pathogen inoculation only. Moreover, AR156 can trigger ISR in sid2-2 and NahG mutants, but not in jar1, ein2 and npr1 mutant plants. Our results indicate that AR156-induced ISR depends on JA/ET-signaling pathway and NPR1, but not SA. Also, AR156-treated plants are able to rapidly activate MAPK signaling and FRK1/WRKY53 gene expression, both of which are involved in pathogen associated molecular pattern (PAMP)-triggered immunity (PTI). The results indicate that AR156 can induce SAR by the JA/ET-signaling pathways in an NPR1-dependent manner and involves multiple PTI components.